2013
DOI: 10.1038/pr.2013.49
|View full text |Cite
|
Sign up to set email alerts
|

Time-related arterial changes after allogeneic hematopoietic stem cell transplantation in children

Abstract: Background: Metabolic syndrome is a frequent late effect in young adults after hematopoietic stem cell transplantation (HSCT) performed in childhood. Methods: To further study the signs of cardiovascular changes in HSCT patients, we performed noninvasive vascular ultrasonic measurements of arterial stiffness and endothelial function in 25 children (median age: 11.2 y) and in 22 healthy matched controls. results: The distensibility of the common carotid artery (CCA) was significantly lower in the patients than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
2
9
1
Order By: Relevance
“…In that study we observed lower carotid vascular function in survivors of leukemia compared to their sibling controls, but no difference in cIMT. Like the present study, Turanlahti et al 19 also did not find any difference in cIMT between HCT survivors and healthy controls. It should be noted that Vatanen et al 18 reported greater cIMT in HCT survivors than healthy controls, but when the HCT survivors were analyzed by treatment (i.e., those who received TBI and those who did not) no significant difference in cIMT was observed between these two HCT treatments and healthy controls.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In that study we observed lower carotid vascular function in survivors of leukemia compared to their sibling controls, but no difference in cIMT. Like the present study, Turanlahti et al 19 also did not find any difference in cIMT between HCT survivors and healthy controls. It should be noted that Vatanen et al 18 reported greater cIMT in HCT survivors than healthy controls, but when the HCT survivors were analyzed by treatment (i.e., those who received TBI and those who did not) no significant difference in cIMT was observed between these two HCT treatments and healthy controls.…”
Section: Discussionsupporting
confidence: 71%
“…However, in this study 13 it is hard to attribute changes in vascular structure and function to one particular treatment exposure due to significant differences in the treatment protocols received. Two other studies 18,19 have also reported no significant difference between HCT survivors and healthy controls in brachial artery endothelial-dependent dilation. As stated at a recent NIH consensus conference on the late effects of pediatric HCT treatments 5 , the degree of cellular damage that occurs in these patients is related to the health status of the pre-HCT recipient, presence of other co-morbidities, and baseline organ function of the recipient at the time of the HCT regimen.…”
Section: Discussionmentioning
confidence: 87%
“…The limited survivor sample size and variance in the irradiation dose and follow‐up precluded analyses between dose, time, and changes in vascular morphology and function. However, previous studies have reported radiation dose thresholds of 30 Gy or more for an increased occurrence of stroke in pediatric brain tumor survivors, and thresholds of more than 20 Gy for development of coronary artery disease in pediatric survivors of Hodgkin lymphoma . Our results indicate significant subclinical vascular damage already at TBI doses of 10–12 Gy.…”
Section: Discussioncontrasting
confidence: 42%
“…Although advanced accelerated carotid artery disease, radiation dose‐dependent IMT thickening, and significant obstruction of the arterial lumen have been reported in adults after local high‐dose radiotherapy, the natural history of radiotherapy‐induced subclinical arterial damage, especially, in pediatric populations remains poorly defined . Nevertheless, increased carotid and femoral IMT and increased occurrence of stroke have been previously reported among irradiated pediatric CNS tumor survivors, as well as in survivors of Hodgkin disease . The recent cohort of childhood cancer survivors also reported an increased IMT outside the primary irradiation field .…”
Section: Discussionmentioning
confidence: 99%
“…Hematopoietic stem cell transplantation, a curative option in several hematologic malignancies, is associated with an increased risk of health conditions, such as cardiovascular and endocrine disorders, metabolic syndrome and subsequent malignancies, requiring systematic and targeted follow-up 60,63. Early arterial mechanical changes were found at young age after allogenic stem cell transplantation in children, including lower distensibility of the common carotid artery, which decreased with time passed after transplantation 63…”
Section: Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%